Colletotrichum sp. causando mancha foliar em Cassia fistula L.: patogenicidade, morfologia, caracterização molecular e controle in vitro - Rabuske, Jessica Emilia (2016)
The species Cassia fistula L., popularly known as chuva-de-ouro, is an exotic arboreta, used for the purpose of urban trees, however, despite its ornamental value, the species has not been the subject of research papers, especially those who involving the diagnosis or description of phytopathogenic microorganisms causing diseases which could cause harm and/or lead to plant death. So after observing symptoms of leaf spots with dark coloring and irregular contour, distributed by the leaf blade, the prior identification of the pathogen was made which attributed the symptoms to the fungal genus Colletotrichum. Thus, this study aimed to determine the pathogenicity of Colletotrichumsp. associated with leaflets of Cassia fistula and characterize morphological, physiological and molecular pathogen to the species level, and to verify the efficiency of in vitro biological control of the fungus. The morphological characterization was performed based on the size of the conidia and the color of the colony on PDA, and the physiological characterization, tested different temperatures, influences the culture medium and the brightness in the pathogen mycelial growth. Molecular identification were sequenced three genomic regions isolated, which are: ITS, elongation factor 1-α and beta-tubulin. In biological control test was used Trichoderma spp. in commercial forms Agrotrich Plus®, Biotrich® and Ecotrich®. In vitro control tests were conducted by paired comparison method of test cultures and the volatile metabolites. The isolates Colletotrichum sp. were pathogenic to Cassia fistula causing leaf spot. In general, Mathur means contributed best responses mycelial growth and sporulation, but both tests show variation between isolates analyzed. The morphological characteristics present great variability, hindering the definition of the species. Most isolates showed conidia with dimensions that can be classified as C. gloeosporioides. The PCR tool was able to identify isolates of C. gloeosporioides starting the amplified product of beta-tubulin and the elongation fator region. However, not all isolates were identified in this manner, suggesting that the species has great variability of the amplified regions. Trichoderma spp., can be exploited as biological control of leaf spot in Cassia fistula. However, it is suggested to carry out in vivo tests to evaluate the antagonistic potential of Trichoderma.